2014
DOI: 10.1039/c3an02062b
|View full text |Cite
|
Sign up to set email alerts
|

A customized Raman system for point-of-care detection of arthropathic crystals in the synovial fluid

Abstract: Monosodium urate (MSU) and calcium pyrophosphate dihydrate (CPPD) are the most frequently observed crystals in joint space, leading to painful arthropathies. Correct diagnosis of the crystal identity is critical for the appropriate course of treatment. In this work, a custom Raman device in combination with a practical and efficient sample preparation method is used for chemically selective diagnosis of MSU and CPPD crystals in an automated fashion. The samples were prepared by a brief enzymatic digestion trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Dissolution of uric acid was confirmed by cross‐polarized imaging at high magnification. Previous research from our group demonstrated that this pretreatment process, including the digestion and the uric acid supplementary buffer, preserves the crystals, as confirmed by the lack of significant difference between crystal counts performed before versus after treatment. It was also affirmed that artifactual nucleation of crystals from the buffer does not occur.…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…Dissolution of uric acid was confirmed by cross‐polarized imaging at high magnification. Previous research from our group demonstrated that this pretreatment process, including the digestion and the uric acid supplementary buffer, preserves the crystals, as confirmed by the lack of significant difference between crystal counts performed before versus after treatment. It was also affirmed that artifactual nucleation of crystals from the buffer does not occur.…”
Section: Methodssupporting
confidence: 52%
“…First, a disposable syringe–microfiltration step was performed, which included a brief digestion and dilution to collect and concentrate crystals for Raman spectroscopic analysis. Second, a Raman spectroscopy step was performed, in which a shoebox‐sized optoelectromechanical system was customized for conducting an automated Raman spectroscopic analysis to identify crystal species, as detailed in a previous publication from our group .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that point of care Raman (POCR) spectroscopy can detect monosodium urate and CPPD crystals with good sensitivity and specificity at concentrations as low as 5 and 2.5 μg/ mL, 25 and 0.1 and 1 μg/mL. 26 The detection limit of Raman spectroscopy is lower than that reported for CCA. Further study using a larger clinical sample set revealed that CPLM and POCR analyses agreed in 89.7% of samples (156 of 174), κ coefficients indicated that POCR and CPLM had excellent agreement in diagnosing gout (0.84 with 95% CI 0.75 to 0.94), and good, but less broad agreement in diagnosing acute CPP crystal arthritis (pseudogout; 0.61 with 95% CI 0.42 to 0.81).…”
Section: Study Identificationmentioning
confidence: 98%
“…Raman spectroscopy is a chemical analysis technique that is 100% specific in fingerprinting species based on the identification of chemical bonds unique to each material. 28 We reviewed four major studies [25][26][27][28] comparing Raman spectroscopy and CPLM. It was found that point of care Raman (POCR) spectroscopy can detect monosodium urate and CPPD crystals with good sensitivity and specificity at concentrations as low as 5 and 2.5 μg/ mL, 25 and 0.1 and 1 μg/mL.…”
Section: Study Identificationmentioning
confidence: 99%